Conflict Management in Academic Libraries in Ghana: A Comparative Study of Sam Jonah, Osagyefo and John Kofi Borsah Libraries - Koufie, C. (University of Ghana, 2018)
Academic libraries, like any other organizations, are likely to encounter conflicts. This survey identified common, causes and types of conflicts encountered by Sam Jonah, Osagyefo and John Kofi Borsah Libraries and examined the conflicts management techniques employed in managing them. The sample for this study was made of two hundred and sixteen respondents selected from three academic libraries through the census sampling method. The study was a descriptive survey. A validated questionnaire and an interview guide were designed and administered to collect data on the occurrence of conflicts and conflicts management strategies. The data collected was analyzed using frequency counts and percentages and content thematic analysis. The findings revealed that the main sources of conflicts were sharing of limited library resources, different interpretation of an individual‟s roles or responsibilities, poor communication channels, lack of respect because of position or rank, resistance to change at workplace, refusal to perform workplace duty, unrealized expectations, pressure to finish work on time, few people taking decisions for the staff, performing duty alone or one man‟s work or “good face”, unclear lines of authority, territorial encroachments, interaction patterns, and lack of job experience by the supervisors. Again, the study revealed that the library management and the members of staff of the academic libraries most often employed avoidance, accommodation, collaboration, compromise and competition as conflict management strategies, though some strategies were more dominant in particular academic library. Based on the findings, it is recommended that academic libraries should give prompt attention to causes of conflicts and their management strategies.
Thesis (MPhil)
Keywords: Management Strategies; Collaboration; Communication; Academic libraries; Accommodation